History narrative construction of product aesthetics: artistic cultural expression from form to emotion - Song Qiao; Yuhong Zhang (Trans/Form/Ação)
This article adopts a combination of literature review and theoretical analysis to explore the relationship between formal aesthetics and emotional expression in product design from the perspective of Eastern and Western philosophy, as well as its narrative construction process. Product aesthetics is not only the result of visual expression, but also forms a multidimensional experience through the construction of form, the realization of function, and the transmission of emotions. The results indicate that the value of product aesthetics lies in its ability to establish a profound connection between form and emotion, creating works that are both visually appealing and touching. This article not only provides a theoretical framework for understanding the relationship between aesthetics and emotional expression in product design, but also provides practical guidance for designers to create products with more emotional value.